2021
DOI: 10.2196/25828
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Health Record–Based Simulation During Intern Boot Camp: Interventional Study

Abstract: Background Accurate data retrieval is an essential part of patient care in the intensive care unit (ICU). The electronic health record (EHR) is the primary method for data storage and data review. We previously reported that residents participating in EHR-based simulations have varied and nonstandard approaches to finding data in the ICU, with subsequent errors in recognizing patient safety issues. We hypothesized that a novel EHR simulation-based training exercise would decrease EHR use variabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…4 Additionally, previous studies reported that high-fidelity simulation-based EHR training allows learners to gain critical EHR skills relevant to their clinical setting while simultaneously being a high-quality educational activity that could mitigate provider burnout. [5][6][7] We applied this paradigm during the operational crisis to rapidly facilitate our redeployment of the advanced practice providers.…”
Section: Workflow-based Ehr Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Additionally, previous studies reported that high-fidelity simulation-based EHR training allows learners to gain critical EHR skills relevant to their clinical setting while simultaneously being a high-quality educational activity that could mitigate provider burnout. [5][6][7] We applied this paradigm during the operational crisis to rapidly facilitate our redeployment of the advanced practice providers.…”
Section: Workflow-based Ehr Trainingmentioning
confidence: 99%
“…and based on prior curricula used for employee onboarding, for in-person training sessions. 5,7,9,10 The curriculum emphasized efficient information retrieval, order entry, note creation, and other strategies to ensure patient safety. The content was prioritized based on the purposed workflow for the CRNAs in the surge ICU as determined by their clinical leader (KB) and knowledge of prior institutional patient safety vulnerabilities from EHR use through an author's institutional patient safety role (JAG).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This model allows for instant debriefing as well as formative and summative feedback and coaching, and promotes retention of concepts learned during the session [ 22 ]. Coupling clinically relevant content to workflows familiar to the learner during EHR training is critical to successfully implementing this stage [ 27 ].…”
Section: What Is Our Model Of Ehr Training?mentioning
confidence: 99%
“…We have previously described the ability to integrate EHRs into high fidelity simulation to understand its usability, also to understand the workflows of multiple professional groups, as well as test the effectiveness of education and onboarding. [9][10][11] Therefore, the purpose of this study was to assess the clinical usability of a comprehensive, rapidly deployable electronic health record in a field intensive care unit, and provide capacity for remote export consultation through the use of simulation.…”
Section: Introductionmentioning
confidence: 99%